The official guide for GMAT review 2016 the most comprehensive study guide, from the creators of the GMAT test : from the graduate managment admission council - Graduate Management Admission Council (Hoboken, NJ Wiley, 2015)
The most comprehensive study guide, from the creators of the test
1.0 What Is the GMAT(R) Exam? 6 1.0 What Is the GMAT(R) Exam? 7 1.1 Why Take the GMAT(R) Exam? 7 1.2 GMAT(R) Exam Format 8 1.3 What Is the Content of the Test Like? 9 1.4 Integrated Reasoning Section 10 1.5 Quantitative Section 10 1.6 Verbal Section 11 1.7 Analytical Writing Assessment 11 1.8 What Computer Skills Will I Need? 11 1.9 What Are the Test Centers Like? 12 1.10 How Are Scores Calculated? 12 1.11 Test Development Process 13 2.0 How to Prepare 14 2.0 How to Prepare 15 2.1 How Should I Prepare to Take the Test? 15 2.2 What About Practice Tests? 15 2.3 How Should I Use the Diagnostic Test? 16 2.4 Where Can I Get Additional Practice? 16 2.5 General Test-Taking Suggestions 16 3.0 Diagnostic Test 18 3.0 Diagnostic Test 19 3.1 Quantitative Questions 20 3.2 Verbal Questions 27 3.3 Quantitative and Verbal Answer Keys 45 3.4 Interpretive Guide 45 3.5 Quantitative Answer Explanations 46 3.6 Verbal Answer Explanations 65 4.0 Math Review 106 4.0 Math Review 107 4.1 Arithmetic 108 4.2 Algebra 120 4.3 Geometry 127 4.4 Word Problems 140 5.0 Problem Solving 148 5.0 Problem Solving 149 5.1 Test-Taking Strategies 150 5.2 The Directions 150 5.3 Practice Questions 152 5.4 Answer Key 186 5.5 Answer Explanations 188 6.0 Data Sufficiency 270 6.0 Data Sufficiency 271 6.1 Test-Taking Strategies 272 6.2 The Directions 274 6.3 Practice Questions 276 6.4 Answer Key 294 6.5 Answer Explanations 295 7.0 Reading Comprehension 360 7.0 Reading Comprehension 361 7.1 What Is Measured 362 7.2 Test-Taking Strategies 364 7.3 The Directions 365 7.4 Practice Questions 366 7.5 Answer Key 419 7.6 Answer Explanations 420 8.0 Critical Reasoning 498 8.0 Critical Reasoning 499 8.1 What Is Measured 500 8.2 Test-Taking Strategies 500 8.3 The Directions 501 8.4 Practice Questions 502 8.5 Answer Key 541 8.6 Answer Explanations 542 9.0 Sentence Correction 666 9.0 Sentence Correction 667 9.1 Basic English Grammar Rules 667 9.2 Study Suggestions 672 9.3 What Is Measured 672 9.4 Test-Taking Strategies 672 9.5 The Directions 673 9.6 Practice Questions 674 9.7 Answer Key 701 9.8 Answer Explanations 702 10.0 Integrated Reasoning 778 10.0 Integrated Reasoning 779 10.1 What Is Measured 779 10.2 The Question Types 780 10.3 Test-Taking Strategies 787 10.4 The Directions 789 11.0 Analytical Writing Assessment 790 11.0 Analytical Writing Assessment 791 11.1 What Is Measured 791 11.2 Test-Taking Strategies 792 11.3 The Directions 792 11.4 GMAT(R) Scoring Guide: Analysis of an Argument 793 11.5 Sample: Analysis of an Argument 795 11.6 Analysis of an Argument Sample Topics 799 Appendix A Answer Sheets 831 Diagnostic Answer Sheet Quantitative 831 Diagnostic Answer Sheet Verbal 831 Problem Solving Answer Sheet 832 Data Sufficiency Answer Sheet 832 Reading Comprehension Answer Sheet 833 Critical Reasoning Answer Sheet 834 Sentence Correction Answer Sheet 835 Integrated Reasoning Answer Sheet 836
New! Create your own practice sets online with 900 questions from past exams with answer explanations ; New! Exclusive online videos with study tips and test-taking strategies ; Diagnostic test helps focus your test-prep efforts
2
Keywords: GMAT; Managementschule